Multidrug resistant Klebsiella Pneumoniae reservoir and their capsular resistance genes in cow farms of district Peshawar, Pakistan. - Saddam Saddam; Muddasir Khan; Muhsin Jamal; Sadeeq Ur Rehman; Petr Slama; Pavel Horky (PLoS ONE, 2023)
Klebsiella pneumoniae is a major zoonotic pathogen that causes a variety of severe illnesses as well as mastitis. The distribution of mastitis-causing K. Pneumoniae and its virulence factors vary by country and geographical location. The present study aimed to find out the occurrence of Multidrug-resistant (MDR) K. Pneumoniae and their capsular resistance genes which were undocumented previously in cow farms of district Peshawar, Pakistan. A total of 700 milk samples from symptomatic mastitic cows were screened for MDR K. Pneumoniae. Furthermore, the characterization of capsular resistance genes was done by molecular techniques. Among these samples, K. pneumoniae was found 180/700 (25.7%), while MDR K. pneumoniae was found 80/180 (44.4%). The antibiogram analysis revealed high resistance to Vancomycin (95%) while highly sensitive to Ceftazidime (80%). The distribution of capsular genes shows the most common serotype K2 gene 39/80 (48.7%), followed by serotype K1 gene 34/80 (42.5%), serotype K5 17/80 (21.2%), and serotype K54 13/80 (16.2), respectively. Moreover, the co-occurrence of serotypes K1+K2 was found at 11.25%, KI+K5 was 05%, K1+K54 was 3.75%, and K2+K5 was 7.5%, respectively. A statistically significant association (p ≤ 0.05) was found between predicted and discovered K. pneumoniae values. In conclusion, the presence of MDR K. pneumoniae in combination with capsular genes may be a possible threat to dairy farm animals and humans in Peshawar, Pakistan. It may give us special attention to follow up on hygienic practices in livestock management.